2020
DOI: 10.1155/2020/8814699
|View full text |Cite
|
Sign up to set email alerts
|

Polyserositis: An Extremely Rare Life-Threatening Manifestation of Pheochromocytoma

Abstract: The pericardium is an uncommon site for manifestation of pheochromocytoma. Herein, the case of a 57-year-old man with cardiac tamponade is presented. Pericardiocentesis was performed, and the vital signs were stabilized afterwards. An abdominal computed tomography (CT) scan illustrated a nonhomogeneous right adrenal mass suspicious of pheochromocytoma, planned for right adrenalectomy. He recovered well after surgery, and his subsequent follow-ups did not reveal any complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Given the young age of the patient and the absence of renal and thyroid abnormalities, connective tissue disease, an underlying haematological malignancy such as acute myelogenous leukaemia and chronic myeloid leukaemia, phaeochromocytoma and sarcoidosis had to be excluded. 9–12 The low ESR and the normal autoimmune screen made connective tissue diseases unlikely. The probability of an underlying lymphoproliferative disorder was also low with a normal blood film and LDH and no significant lymphadenopathy on CT scan.…”
Section: Discussionmentioning
confidence: 99%
“…Given the young age of the patient and the absence of renal and thyroid abnormalities, connective tissue disease, an underlying haematological malignancy such as acute myelogenous leukaemia and chronic myeloid leukaemia, phaeochromocytoma and sarcoidosis had to be excluded. 9–12 The low ESR and the normal autoimmune screen made connective tissue diseases unlikely. The probability of an underlying lymphoproliferative disorder was also low with a normal blood film and LDH and no significant lymphadenopathy on CT scan.…”
Section: Discussionmentioning
confidence: 99%
“…Although this is not impossible, it rarely happens. e average annual incidence of GBS was 1 per 100 000 patient-years, while the incidence of pheochromocytoma are approximately 0.8 per 100 000 patient-years [5,17]. Abdel-Salam et al reported the case of GBS with subsequent pheochromocytoma [17].…”
Section: Discussionmentioning
confidence: 99%
“…Less often, the tumor will cause severe cardiovascular complications such as myocardial infarction, arrhythmias, pericardial effusion, and congestive heart failure. Pheochromocytoma-induced cardiomyopathy is similar to Takotsubo cardiomyopathy and myocarditis [4,5]. Diagnosis of pheochromocytoma-related cardiomyopathies is often delayed because of the atypical presentation.…”
Section: Introductionmentioning
confidence: 99%